An Assessment of Wind Energy Potential for Selected Sites in Malaysia Using Feed-In Tariff Criteria. Issue 3 (June 2014) - Albani, A.; Ibrahim, M. Z.
Malaysia is still dependent on non-renewable sources like coal and diesel to generate electricity. However, Malaysia has taken steps to explore the renewable energy (RE) as an alternative source for generating electricity. This paper presents the simulation of micrositing analysis by using WindPRO software and feed-in tariff (FiT) rates. Four sites were indentified: Kuala Terengganu, Mersing, Kudat, and Langkawi Island. Wind data of year 2009 were obtained from Malaysian Meteorological Department (MMD) stations. The 22 kW wind turbine was selected for energy calculation. Forty-six wind farms in the range 22 kW to 1, 012 kW were simulated, taking into consideration sites' roughnesses and wind resources. The optimal feed-in tariffs (FiT) rates were identified as that gives the maximum profit to the investors. Both Mersing and Kudat showed the lowest value of FiT rates: RM0.85/kWh to RM0.86/kWh, and RM0.85/kWh to RM0.87/kWh, respectively. Whereas, the sites Kuala Terengganu and Langkawi Island had FiT rates: RM1.10/kWh to RM1.28/kWh, and RM1.15/kWh to RM1.42/kWh, respectively. Finally, the overall results in this study show Malaysia has potential for developing small to medium scale wind farms.